Prostaglandin E2 as a potent therapeutic target for treatment of colon cancer - Karpisheh, Vahid; Nikkhoo, Afshin; Hojjat-Farsangi, Mohammad; Namdar, Afshin; Azizi, Gholamreza; Ghalamfarsa, Ghasem; Sabz, Gholamabas; Yousefi, Mehdi; Yousefi, Bahman; Jadidi-Niaragh, Farhad (Prostaglandins & other lipid mediators, 2019)
•Colon cancer in one of the main health-related problems which is incurable particularly in advanced stages.•Prostanoids and particularly prostaglandin E2 (PGE2) are important inflammatory lipid mediators.•PGE2 plays an important role in tumorigenesis process of colon cancer.•PGE2 can be considered as potent therapeutic target for colon cancer therapy. Although colon cancer is one of the most important triggers of cancer related mortality, a few therapeutic options exist for this disease, including combination chemotherapy, anti-EGFR and anti-angiogenic agents. However, none of these therapeutics are fully effective for complete remission, and this issue needs further investigations, particularly in the patients with advanced disease. It has been shown that colon carcinogenesis process is associated with upregulation of prostaglandin (PG) levels. Moreover, conversion of pre-malignant cells to malignant was also related with increased generation of PGs in susceptible subjects. Among the prostanoids, PGE2 is the most important produced member which generated in high levels by colon tumor cells. Generation of PGE2 by action of cyclooxygenase (COX)-2 can promote growth and development, resistance to apoptosis, proliferation, invasion and metastasis, angiogenesis and drug resistance in colon cancer. Increased levels of PGE2 and COX-2 in colon cancer is reported by various investigators which was associated with disease progression. It is suggested that there is a positive feedback loop between COX-2 and PGE2, in which function of COX-2 induces generation of PGE2, and upregulation of PGE2 increases the expression of COX-2 in colon cancer. Although an existence of this feedback loop is well-documented, its precise mechanism, signaling pathways, and the particular E-type prostanoid (EP) receptor mediating this feedback are elusive. Therefore, it seems that targeting COX-2/PGE2/EP receptors may be supposed as a potent therapeutic strategy for treatment of colon cancer. In this review, we try to clarify the role of PGE2 in cancer progression and its targeting for treatment of colon cancer.